Review of Theodore Gracyk and Andrew Kania, eds. 2011. The Routledge Companion to Philosophy and Music. Abingdon, UK, and New York, NY: Routledge. - Gleason, Scott (Current Musicology, 2012)
At least since Plato the problematic of philosophizing about music, or even conceiving a kind of musical philosophy, has conditioned our discourses. The Routledge Companion to Philosophy and Music shares in this problematic but raises its stakes, encouraging us to renew our attempts to think music philosophically. It accomplishes its primary goal admirably: it could very well accompany discussions of music and philosophy for some time to come. The articles it contains are for the most part emphatically if not explicitly written from the perspective of analytic philosophy, which suggests certain disciplinary alignments: music theory and cognition seem to align easily with analytic philosophy, whereas ethnomusicology and historical musicology seem to align with continental philosophy. One of the strengths of the Companion is its ability to appeal to readers from seemingly every music–academic discipline. The Companion thus provides a new standard of philosophical conversation toward which musicians can aspire.